Filovirus Disease Outbreaks: A Chronological Overview. Issue 1 (June 2019) - Languon, Sylvester; Quaye, Osbourne
Filoviruses cause outbreaks which lead to high fatality in humans and non-human primates, thus tagging them as major threats to public health and species conservation. In this review, we give account of index cases responsible for filovirus disease outbreaks that have occurred over the past 52 years in a chronological fashion, by describing the circumstances that led to the outbreaks, and how each of the outbreaks broke out. Since the discovery of Marburg virus and Ebola virus in 1967 and 1976, respectively, more than 40 filovirus disease outbreaks have been reported; majority of which have occurred in Africa. The chronological presentation of this review is to provide a concise overview of filovirus disease outbreaks since the discovery of the viruses, and highlight the patterns in the occurrence of the outbreaks. This review will help researchers to better appreciate the need for surveillance, especially in areas where there have been no filovirus disease outbreaks. We conclude by summarizing some recommendations that have been proposed by health and policy decision makers over the years.